Additional notes on Mabea angularis Hollander (Euphorbiaceae), first record for the State of Pará, Brazil - Trindade, Maria José de Sousa; Secco, Ricardo de Souza (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2009)
Mabea angularis Hollander is a new record for the State of Pará. The first description of its flowers, which were unknown in the literature, is presented.